TCR T cells overexpressing c-Jun have better functionality with improved tumor infiltration and persistence in hepatocellular carcinoma - Hussein, Mohamed S.; Li, Qi; Mao, Rui; Peng, Yibing; He, Yukai (Frontiers in Immunology, 2023)
Background: The overall 5-year survival rate of hepatocellular carcinoma (HCC), a major form of liver cancer, is merely 20%, underscoring the need for more effective therapies. We recently identified T cell receptors (TCR) specific for the HLA-A2/alpha fetoprotein amino acids 158-166 (AFP158) and showed that these TCR engineered T cells could control HCC xenografts in NSG mice. However, their efficacy was limited by poor expansion, loss of function, and short persistence of the TCR T cells. Here, we studied whether overexpression of c-Jun, a transcription factor required for T cell activation, in the TCR T cells could enhance their expansion, function, and persistence in HCC tumor models. Methods: Recombinant lentiviral vectors (lv), expressing either the HLA-A2/AFP158-specific TCR or both the TCR and c-Jun (TCR-JUN), were constructed and used to transduce primary human T cells to generate the TCR or TCR-JUN T cells, respectively. We compared the expansion, effector function, and exhaustion status of the TCR and TCR-JUN T cells in vitro after HCC tumor stimulation. Additionally, we studied the persistence and antitumor effects of the TCR and TCR-JUN T cells using the HCC xenografts in NSG mice. Results: We could effectively transduce primary human T cells to express both TCR and c-Jun. Compared to the HLA-A2/AFP158 TCR T cells, the TCR-JUN T cells have better expansion potential in culture, with enhanced functional capacity against HCC tumor cells. In addition, the TCR-JUN T cells were less apoptotic and more resistant to exhaustion after HepG2 tumor stimulation. In the HCC xenograft tumor model, c-Jun overexpression enhanced the TCR T cell expansion and increased the overall survival rate of the treated mice. Importantly, the TCR-JUN T cells were less exhausted in the tumor lesions and demonstrated enhanced tumor infiltration, functionality, and persistence. Conclusion: c-Jun overexpression can enhance the expansion, function, and persistence of the A2/AFP158 TCR engineered T cells. The c-Jun gene co-delivery has the potential to enhance the antitumor efficacy of AFP specific TCR T cells when treating patients with HCC.